Opposite Aerosol Index‐Cloud Droplet Effective Radius Correlations Over Major Industrial Regions and Their Adjacent Oceans. Issue 11 (13th June 2018) - Ma, X.; Jia, H.; Yu, F.; Quaas, J.
Abstract: The Moderate Resolution Imaging Spectroradiometer (MODIS) C6 L3 and the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim reanalysis data from 2003 to 2016 are employed to study aerosol‐cloud correlations over three industrial regions and their adjacent oceans, as well as explore the impact of meteorological conditions on the correlations. The analysis focusing on liquid and single‐layer clouds indicates an opposite aerosol‐cloud correlation between land and ocean; namely, cloud effective radius is positively correlated with aerosol index over industrial regions (positive slopes), but negatively correlated over their adjacent oceans (negative slopes), for a quasi‐constant liquid water path. The positive slopes are relatively large under low lower‐tropospheric stability (LTS; weakly stable condition), but much weaker or even become negative under high LTS (stable conditions) and high liquid water path. The occurrence frequency of cloud top height (CTH) and LTS suggests that positive correlations are more likely corresponding to relatively high CTH and low LTS, while negative to low CTH and high LTS. Plain Language Summary: Aerosol‐cloud interactions play an important role in climate prediction, but remain to have large uncertainties. The major industrial regions generally exhibit relatively high aerosol concentrations, and how aerosols impact cloud properties, and how aerosol‐cloud interactions modulate cloud and precipitation processes, is an interesting and challenging topic. In this study, a new retrieval from long‐ term satellite data is employed to examine the correlation between aerosol concentration and cloud droplet size over the three industrial regions and their adjacent oceans. The results show the opposite aerosol‐cloud correlation between land and ocean. Positive slopes are more likely associated with high cloud top height and low lower‐tropospheric stability. This finding is very useful to the communities for an accurate prediction of weather and climate. Key Points: Cloud effective radius is positively correlated to aerosol index over three industrial regions, but negatively over adjacent oceans Positive slopes over land are relatively large under low lower‐tropospheric stability (LTS), but much weaker or negative under high LTS Positive correlations possibly correspond to relatively high cloud top height (CTH) and low LTS, while negative to low CTH and high LTS